Burden of leishmaniasis in Brazil and federated units, 1990-2016: Findings from Global Burden of Disease Study 2016 - Bezerra, Juliana Maria Trindade; de Araújo, Valdelaine Etelvina Miranda; Barbosa, David Soeiro; Martins-Melo, Francisco Rogerlândio; Werneck, Guilherme Loureiro; Carneiro, Mariângela (PLOS Neglected Tropical Diseases, 2018)
Author summary Leishmaniasis are diseases caused by obligatory intracellular parasites of the genus Leishmania and are transmitted to humans through the bite of female sandflies during blood repast. Untreated visceral leishmaniasis can lead to death, while cutaneous and mucocutaneous forms generally do not pose risk of death but can cause disability and permanent injury, which raises stigma and social prejudice. The Global Burden of Disease Study (GBD) is a systematic and scientific effort to quantify the health loss caused by infectious and non-infectious diseases and injury and their risk factors categorized by age, sex, and geographic distribution at specific periods of time. The present article describes, for the first time, the burden of leishmaniasis in the 27 Brazilian federated units. The VL burden increased in some states in the Northeast and Southeast regions and decreased for CML in some Northern states. Understanding the burden of these diseases and their regional differences is of great relevance for the establishment of adequate and region-specific surveillance and control measures. In addition, it can help in the rational use of available resources and in decision making aimed at reducing the transmission of the parasite and the burden of this disabling and potentially lethal disease.